Application of horizontal flow prefiltration and slow sand filtration for small community water supply - Vichian Udomratanasilpa; Nguyen, Cong Thanh; Vigneswaran, Saravanamuthu; Samorn Muttamara; Carl Duisburg Gesellschaft, e.v. (COG) Government of the Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1984)
An attempt was made on a pilot scale to fi nd a simple mod el for a horizontal flow roughing prefilter used with slow sand filter a s the water treatment system for a s mall community. Three different lengths of horizontal p refilter PVC pipe model of 250 mm in diameter, i.e. 2. 0 m, 3.0 m, 4.0 m, were used in this study at the filtration rate of 1.25 m /m - h . Crushed stone , with effective size of 2-20 mm, and coconut husk fiber were used as roughing filter media in the horizontal prefilters. Slow sand filters with the filtration r ate of 0. 15 m /m-h we reused t o polish water from the horizontal prefilters. It was found that the performance of horizontal prefilters using single crushed stones was less effective than those using dual media , coconut fiber 80 cm in .length followed by crushed stones. The horizontal prefilter of 4.0 m length performs best in filtering the raw water in this study The fraction of coconut fiber in horizontal prefilter can perform effectively tor a .bout one month. Turbidity and suspended solids removal efficiencies in horizontal prefilter, when single medium was used, were a bout 28-68 % and 45-95 % whereas in the horizontal pref1lter with dual media turbidity and suspended solids removal efficiencies were about 30-68 % and 54-98 %. The reduction of fil54qgili5y indices of raw water when passing through the horizontal prefilters was about 85 % The slow sand filters can treat the water to meet the WHO standard drinking Water in terms of turbidity and completely removed suspended solids on occasions. The overall removal efficiencies of this system were about 71 -94 % and 81 -99. 6 % for turbidity and suspended solids respectively.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1984
Keywords: Filters and filtration